Outcome Evaluation of Percutaneous Coronary Intervention vs Medical Therapy Alone in Patients with Chronic Coronary Syndrome - Hsien-Yuan Chang; Hsin-Yu Fang; Mu-Shiang Huang; You-Zhen Chen; Di-Yung Chen; Edward Chia-Cheng Lai; Jung-Der Wang; Yi-Heng Li; Li-Jung Elizabeth Ku (Journal of Food and Drug Analysis, 2026)
This study provides real-world evidence by comparing the long-term clinical outcomes of percutaneous coronary intervention (PCI) versus medical therapy alone in patients with chronic coronary syndrome (CCS) diagnosed non-invasively, given the lack of evidence in this population. This retrospective cohort study (2013-2018) utilized data from a medical center’s Cardiovascular Disease Databank, which was linked to national mortality records in Taiwan. Propensity score matching (PSM) and stabilized inverse probability of treatment weighting (IPTW) were applied to adjust for baseline differences between the PCI and medication-only groups. Major adverse cardiovascular events (MACE), including all-cause mortality, non-fatal myocardial infarction (MI), and revascularization, were compared between groups. After 1:4 propensity score matching, a total of 4,369 patients were included (PCI, N=1,058; medication only, N=3,311). Adjusted Cox proportional hazards models showed that the PCI group had a higher hazard of MACE (aHR, 1.38 [95% CI, 1.22-1.56]), primarily driven by increased revascularization (aHR, 1.65 [95% CI, 1.39-1.95]), compared to the medication-only groups. No significant differences were observed in all-cause mortality (aHR, 1.13 [95% CI, 0.96-1.34]) or MI (aHR, 1.08 [95% CI, 0.77-1.52]). Furthermore, the mean total healthcare cost during the index year was US$3,232 (SD = 9,896) for the medication-only group, compared with US$10,931 (SD = 8,781) for the PCI group. Among CCS patients diagnosed non-invasively, the medication-only group demonstrated comparable all-cause mortality and MI rates, but a significantly lower risk of revascularization compared with the PCI group, while incurring only one-third of the healthcare costs. Clinicians should carefully evaluate the benefits and risks of stent placement in CCS patients.